Neuroendocrine Pathways Mediating Nutritional Acceleration of Puberty: Insights from Ruminant Models - Amstalden, Marcel; Alves, Bruna R.; Liu, Songrui; Cardoso, Rodolfo C.; Williams, Gary L. (Frontiers in Endocrinology, 2011)
The pubertal process is characterized by an activation of physiological events within the hypothalamic-adenohypophyseal–gonadal axis which culminate in reproductive competence. Excessive weight gain and adiposity during the juvenile period is associated with accelerated onset of puberty in females. The mechanisms and pathways by which excess energy balance advances puberty are unclear, but appear to involve an early escape from estradiol negative feedback and early initiation of high-frequency episodic gonadotropin-releasing hormone (GnRH) secretion. Hypothalamic neurons, particularly neuropeptide Y and proopiomelanocortin neurons are likely important components of the pathway sensing and transmitting metabolic information to the control of GnRH secretion. Kisspeptin neurons may also have a role as effector neurons integrating metabolic and gonadal steroid feedback effects on GnRH secretion at the time of puberty. Recent studies indicate that leptin-responsive neurons within the ventral premammillary nucleus play a critical role in pubertal progression and challenge the relevance of kisspeptin neurons in this process. Nevertheless, the nutritional control of puberty is likely to involve an integration of major sensor and effector pathways that interact with modulatory circuitries for a fine control of GnRH neuron function. In this review, observations made in ruminant species are emphasized for a comparative perspective.